Investigação do potencial antifúngico do trans-anetol sobre cepas de Candida glabrata e Candida parapsilosis: uma abordagem in vitro e in silico - Santos, José Roberto Dantas de Andrade (2024)
Approximately 1.5 million people die annually from invasive fungal infections globally, with about 80% of these deaths resulting from opportunistic fungal infections acquired in hospitals, predominantly caused by Candida species. Plants, such as star anise (Illicium verum), are sources of compounds with broad biological activity, including antifungal action. Star anise contains various chemical constituents, such as phenylpropanoids, sesquiterpene lactones, flavonoids, and phenolic acids, and demonstrates broad-spectrum antifungal activity. This spice is effective in inhibiting food spoilage by Aspergillus and Fusarium, and also possesses antibacterial and antioxidant properties. However, detailed studies on the use of star anise as an antifungal agent are lacking, particularly regarding the active components and their mechanisms of action. This work investigates the antifungal potential of trans-anethole, the main component of star anise essential oil, and explores its possible mechanisms of action against Candida glabrata and Candida parapsilosis strains. For this purpose, minimum inhibitory concentrations (MICs) and minimum fungicidal concentrations (MFCs) were assessed using the broth microdilution technique. The antifungal potential of trans-anethole in synergy with fluconazole was evaluated using a checkerboard assay. Possible mechanisms of action were investigated using sorbitol and ergosterol assays, which assess interactions with the cell wall and membrane, respectively. Furthermore, molecular docking evaluated the interactions of TA with Pdr5, a drug efflux pump protein. The main results of this study indicated good antifungal activity of trans-anethole against both Candida species. The MIC of trans-anethole for Candida glabrata ranged from 128 μg/mL to 1024 μg/mL and from 128 μg/mL to 512 μg/mL for Candida parapsilosis. The checkerboard assay demonstrated synergistic activity between trans-anethole and fluconazole. The fractional inhibitory concentration index (FICI) was 0.5 for Candida glabrata and 0.375 for Candida parapsilosis. However, the mechanism of action assay could not pinpoint the exact pathway used by transanethole to produce the observed effect. Molecular docking studies revealed an interaction between the active site of Pdr5 and trans-anethole, with predominant hydrophobic interactions and the oxygen of the methoxy group of trans-anethole interacting with Tyr356 of the protein's active site. Taken together, the findings of this study highlight the antifungal potential of trans-anethole as a standalone antifungal agent and, particularly, in combination with fluconazole, showing promising activity that may aid in the practical application of combined therapies aimed at overcoming antifungal resistance.